Airflow ejection-wrapped clamping type seedling picking method and parameter optimization - Ma, Guoxin; Chen, Xi; Liu, Yang; Han, Luhua; Mao, Hanping; Hu, Jianping (Frontiers in Plant Science, 2023)
Since the current clamp-type and push-out-type seedling picking method would bring damage to seedlings, this study aimed to proposed an airflow ejection-wrapped clamping type seedling picking method, which used airflow to eject out seedling and the seedlings would be wrapped clamped to reduce the damage of seedlings during seedling picking process. The operation form of airflow nozzle device was determined according to the plug tray, and the air tightness during airflow ejection process could be guaranteed with a soft sucker installed in the top of airflow nozzle. The diameter of the airflow nozzle was selected as 3.5 mm to match with the drainage outlet of the plug tray, and the airflow pressure which could eject out seedlings was calculated as 0.146 Mpa~0.315 Mpa on the basis of gas jet dynamic. The fluid-solid coupling simulation of airflow ejection in Comsol proposed that the seedlings could be ejected out under the airflow pressure was equal to or greater than 0.4 Mpa, and the airflow should be maintained for about 0.3 s to ensure the posture of the seedlings ejected out for better seedling clamping. The further fluid-discrete body simulation of airflow ejection by using Fluent-Edem coupling method indicated that the seedling would be damaged under airflow pressure of 0.5 MPa, so the airflow pressure should be set as 0.4 MPa during seedling ejection process. Besides, a wrapped clamping type which clamped the seedlings from all sides in the form of flexible package was also designed to match with the airflow ejection method, and the RecurDyn-Edem coupling simulation shown that the end-effector could tightly clamp the seedling without damage when the angle between the clamping slices and the vertical direction was 8.5°. Finally, the airflow ejection-wrapped clamping type seedling picking device was manufactured, and the verification tests verified the simulation results. This research can provide some references for the automatic seedling picking technology.